Can endocan serve as a molecular "hepatostat" in liver regeneration? - Sinan Efe Yazici; Mustafa Emre Gedik; Can Berk Leblebici; Kemal Kosemehmetoglu; Gurcan Gunaydin; Ahmet Bulent Dogrul (BMC, 2023)
Abstract Background Intriguingly, liver regeneration after injury does not induce uncontrolled growth and the underlying mechanisms of such a "hepatostat" are still not clear. Endocan, a proteoglycan, was implicated in liver regeneration. It can support the function of hepatocyte growth factor/scatter factor in tissue repair after injury. Endostatin, a 20 kDa C-terminal fragment of collagen XVIII, may modulate the cessation of liver regeneration. eEF2K, a protein kinase that regulates protein synthesis, can regulate angiogenesis. Thus, we investigated the role of endocan, endostatin and eEF2K during normal liver regeneration. Methods Serum samples and regenerating remnant liver tissues were obtained on various days after partial hepatectomy in rats. mRNA expression levels of Vegf and Pcna were analyzed in addition to immunohistochemical evaluations. Liver tissue protein levels of endostatin, endocan and p-eEF2K/eEF2K were determined with Western blot. Serum levels of endostatin and endocan were assessed with ELISA. Results Pcna expression level in residual liver tissues peaked on day-1, while Vegf expression reached its highest level on days 1-3 after partial hepatectomy (70%). Endocan activity declined gradually on days 1-7. The decrease in liver endocan expression was accompanied by an increase in serum endocan levels. Partial hepatectomy induced a rapid increase in liver endostatin levels. Following its surge on day-1, endostatin expression gradually declined, which was accompanied by a peak in serum endostatin. Finally, partial hepatectomy was shown to regulate eEF2K; thus, increasing protein translation. Conclusions We revealed possible mechanistic insights into liver regeneration by examining the associations of Pcna, Vegf, endocan, endostatin, eEF2K with hepatic regeneration after partial hepatectomy. Indeed, endocan might serve as a useful biomarker to monitor clinical prognosis in a plethora of conditions such as recovery of donor's remaining liver after living-donor liver transplant. Whether endocan might represent a strategy to optimize liver regeneration when given therapeutically needs to be investigated in future studies.